2021
DOI: 10.3390/jcdd8110143
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Glucagon-like Peptide-1 and a Th2 Shift May Support Reduced Prevalence of Thoracic Aortic Aneurysm in Patients with Diabetes

Abstract: Glucagon-like peptide-1 (GLP-1) regulates processes involved in the pathophysiology of thoracic aortic aneurysms (TAAs), including inflammation, while protecting against aortic aneurysms in animal models. Type 2 diabetes (T2D) involves altered GLP-1 signaling due to pathology and/or therapy and is associated with reduced prevalence of TAAs. We aimed to assess whether T2D alters the inflammatory profile/proteolytic activity, possible correlations to elevated fasting GLP-1 (F-GLP-1), and its relevance for TAA. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In contrast, other groups have found that CD4 + T cells in aortic aneurysms are predominantly IL-4-producing Th2 cells. Ntika et al ( 49 ) reported that no change was observed in the Th1 cytokines in the TAA group; however, cytokines associated with Th2 cells, such as IL-4, IL-5, and IL-10, were significantly altered in TAA patients compared to the control individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other groups have found that CD4 + T cells in aortic aneurysms are predominantly IL-4-producing Th2 cells. Ntika et al ( 49 ) reported that no change was observed in the Th1 cytokines in the TAA group; however, cytokines associated with Th2 cells, such as IL-4, IL-5, and IL-10, were significantly altered in TAA patients compared to the control individuals.…”
Section: Discussionmentioning
confidence: 99%